An Investigation into the Association Between Inflammatory Bowel Disease and Cardiac Arrhythmias: An Examination of the United States National Inpatient Sample Database. Issue 14 (October 2020) - Mubasher, Mahmood; Syed, Tausif; Hanafi, Amir; Yu, Zhao; Yusuf, Ibrahim; Abdullah, Abdullah Sayied; Mohamed, Mouhand FH; Alweis, Richard; Rao, Mohan; Hoefen, Ryan; Danjuma, Mohammed I
Background: Inflammatory bowel diseases (IBD) associated-chronic inflammation and autonomic dysregulation may predispose to arrhythmias. However, its exact prevalence is unknown. Thus, we aimed to ascertain the prevalence of arrhythmias in patients with IBD. Methods: We queried the Nationwide Inpatient Sample (the largest publicly available all-payer inpatient USA database) from 2012 to 2014. We used the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9 CM) discharge codes to identify adult patients (⩾18 years) with IBD and dysrhythmias (supraventricular tachycardia (SVT), atrial fibrillation, atrial flutter, ventricular tachycardia (VT), or ventricular fibrillation). Furthermore, we identified risk factors for cardiovascular disease. We divided patients into 2 cohorts, IBD cohorts, and non-IBD cohort. The independent effect of a diagnosis of IBD on the risk of dysrhythmias was examined using a multivariable logistic regression model controlling for multiple confounders. Results: We identified 847 235 and 84 757 349 weighted hospitalizations among patients with IBD and non-IBD cohorts, respectively. Patients with IBD were less likely to be hospitalized for dysrhythmias than the non-IBD (9.7% vs 14.2%, P < .001). The hospitalization odds for dysrhythmias among patients with IBD were less than the general population (OR 0.87; 95% CI 0.85-0.88). However, the prevalence of SVT and VT was indifferent between the 2 groups. Male sex, age of over 60, and white race were risk factors for dysrhythmias. Conclusion: Despite prior reports of a higher prevalence of arrhythmias among patients with IBD, in a nationwide inpatient database, we found lower rates of hospitalization-related-arrhythmias in the IBD population compared to that of the general population.